Динамічні процеси у віброударних системах зі змінними параметрами - Костенко, Юрій Вікторович (НТУ "ХПІ", 2016)
Викладений новий підхід до урахування впливу змінної маси технологічного вантажу на характер динамічних процесів у віброударній системі. Встановлено, що внаслідок нелінійної жорсткості пружних опор та залежно від їх конструктивного виконання, можливою є реалізація субгармонійних режимів. Сформульовані критерії для відлаштування від резонансу, що може виникнути на кратних (дольних) частотах збудження. Створена удосконалена конструкція корпусу віброударної машини.

In this paper new approach to the accounting of the variable mass influence on the character of dynamical processes in vibroimpact systems was presented. The purpose of the work is to study the dynamical processes and related effects in vibroimpact systems. To solve the problem was used methods of the oscillation theory, the theory of elasticity, thetheory of 3D parametric shell and solid geometry modelling, finite elements method, the acceleration method. The dependences, that describes the mass change character, based on experimental researches and dependence from dissipated energy were proposed. The accuracy and correctness of approach based on energy dependent was shown. The comparison between traditional and proposed approaches was demonstrated and its advantages and disadvantages was shown. It was found that the realization of sybharmonical modes became possible because of elastic supports nonlinearity and design features. The realization of subharmonical modes lead to growth of impact interaction force. The approach, based on corresponding values for phase variables at the beginning and the end of period was proposed to periodic solutions search. The criteria for tuning from resonance frequencies that can appear on perturbing force with multiple (partite) frequencies were formulated. The machine body designed with taking to the account previously formulated recommendations was created. The investigation of stress-strain status was performed and found that improved machine body satisfies strength requirements. The comparison of numerical and experimental data was done. The accuracy and authenticity of numerical investigations was confirmed.
Dynamic processes in vibroimpact systems with variable parameters
Keywords: міцність машин; вібромашина; змінна маса; прикладна теорія коливань; субгармонійний режим; strength of machines; vibromachine; variable mass